Behaviours of existing shield tunnels due to tunnelling underneath considering asymmetric ground settlements - Xiaolu Gan; Jianlin Yu; Xiaonan Gong; Nianwu Liu; Dongzhu Zheng (Underground Space, 2022)
New tunnelling underneath could influence existing shield tunnels in underground spaces. The evaluation of the influences of tunnelling-induced ground movements on existing tunnels has been a major concern during urban construction. This paper presents a two-stage analytical method that considers the asymmetric ground settlement for investigating the longitudinal tunnel responses to new tunnelling. An improved semi-analytical solution considering the horizontal movement of the new tunnel is established for evaluating the tunnelling-induced asymmetric greenfield settlement. The proposed method is verified with field measurement data from a case study. A parametric analysis is conducted to study the influences of the input parameters on the tunnel responses. Results indicate that the horizontal movement of the new tunnel due to bias loading or asymmetric construction may lead to asymmetric responses of the existing tunnel. With increasing tunnel horizontal movement, the asymmetry of the tunnel responses becomes more obvious. An increase in the pillar depth and decreases in the tunnel horizontal movement and skew angle lower the internal forces induced by new tunnelling.